BET proteins are a key component of immunoglobulin gene expression. (April 2017) - Shim, Jung Min; Lee, Jin S; Russell, Kirsty E; Wiegman, Coen H; Barnes, Peter J; Fear, David; Adcock, Ian M; Durham, Andrew L
Aim: BET proteins have been shown to regulate gene expression including inflammatory genes.Methods: In order to investigate the role of the BET proteins in immunoglobulin production we treated the human B-cell line CLNH11.4 and primary human B cells and ozone-exposed mice with BET inhibitors (JQ1 or IBET151).Results: Both proliferation and IgG production were reduced by JQ1 in a concentration-dependent manner. JQ1 significantly reduced immunoglobulin gene transcription. In vivo treatment of ozone-exposed mice with the BET inhibitor IBET151 similarly inhibited ozone-induced immunoglobulin production. JQ1 did not reduce the protein levels of Brd4 or Oct2 per se but reduced the ability of Brd4 and Oct2 to co-immunoprecipitate and of Oct2 to bind to immunoglobulin gene promoters.Conclusion: Our results indicate that BET proteins including Brd4 play a crucial role regulation B-cell-specific gene expression and immunoglobulin production.